2014
DOI: 10.1016/j.cmet.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Central Neural Regulation of Brown Adipose Tissue Thermogenesis and Energy Expenditure

Abstract: SUMMARY Thermogenesis, the production of heat energy, is the specific, neurally-regulated, metabolic function of brown adipose tissue (BAT) and contributes to the maintenance of body temperature during cold exposure and to the elevated core temperature during several behavioral states, including wakefulness, the acute phase response (fever), and stress. BAT energy expenditure requires metabolic fuel availability and contributes to energy balance. This review summarizes the functional organization and neurochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
415
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(445 citation statements)
references
References 138 publications
(236 reference statements)
14
415
1
15
Order By: Relevance
“…Chronic co-treatment with betahistine also reversed the attenuated BAT UCP 1 and PGC-1α expressions, which illustrated that the two biomarkers of thermogenesis were involved in the decreased energy expenditure and increased weight gain induced by chronic olanzapine treatment [65]. Furthermore, the negative correlation between hypothalamic pAMPKα, and BAT UCP 1 and PGC-1α levels, is in line with the previous report about hypothalamic AMPK modulating BAT thermogenesis, and UCP 1 and PGC-1α expression [184][185][186][187].…”
Section: The Mechanisms Underlying Betahistine In Reducing Antipsychosupporting
confidence: 79%
“…Chronic co-treatment with betahistine also reversed the attenuated BAT UCP 1 and PGC-1α expressions, which illustrated that the two biomarkers of thermogenesis were involved in the decreased energy expenditure and increased weight gain induced by chronic olanzapine treatment [65]. Furthermore, the negative correlation between hypothalamic pAMPKα, and BAT UCP 1 and PGC-1α levels, is in line with the previous report about hypothalamic AMPK modulating BAT thermogenesis, and UCP 1 and PGC-1α expression [184][185][186][187].…”
Section: The Mechanisms Underlying Betahistine In Reducing Antipsychosupporting
confidence: 79%
“…The DMH is a key hypothalamic region governing SNS stimulation of BAT thermogenesis (13,14). Consistent with histology showing inactive BAT in mDMHGsKO mice ( Figure 1H), expression of several BAT genes involved in thermogenesis, including those for PPARγ coactivator 1-α (Pgc1a), cytochrome c ( Figure 4A), and uncoupling protein 1 (Ucp1) ( Figure 4D , RT) were significantly reduced in mDMHGsKO mice.…”
Section: G S α Is Imprinted In Dmhsupporting
confidence: 54%
“…The DMH contains neurons that are polysynaptically connected to BAT via the rostral raphe pallidus and that stimulate SNS activity to BAT, resulting in induction of Ucp1, increased lipid oxi- dation, and thermogenesis (14,(31)(32)(33)(34). We observed that mDMHGsKO mice had an inactive BAT appearance and reduced expression of thermogenic genes in BAT (e.g., Pgc1a, cytochrome c, and Ucp1), and similar BAT histology was observed in DMH-MC4RKO mice.…”
Section: Discussionmentioning
confidence: 56%
“…The current study is, to the best of our knowledge, the first to show that central UGN infusion reduces body weight and adiposity in DIO mice independent of food intake. Indeed, many peripheral signals have been attributed to the regulation of energy expenditure via neuronal pathways, and increasing evidence indicates that BAT activity (23,24) and activation of beige/brown-in-white adipocytes in WAT, a process known as browning (25-27), are controlled by the CNS. Our findings suggest that the mechanisms by which central UGN infusion reduces body weight involve increased energy expenditure through promotion of BAT thermogenesis and the browning of WAT.…”
Section: Discussionmentioning
confidence: 99%